Pengelolaan Situs Web Program Studi Sastra Indonesia Universitas Jambi Sebagai Media Informasi Publik - Mestika Putra, Yoga; Septa Wilyanti, Liza; Izar, Julisah; Wulandari, Sovia; Triandana, Anggi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
: In the digital era, the existence of a website for a university study program is important. With a website that can be accessed anywhere and at any time, the public can find out information and everything related to the study program. The Jambi University Indonesian Literature Study Program website has been designed by the team with the page https://sastraindonesia.unja.ac.id. However, the website is not managed well so the information presented has not been updated. Apart from that, the layout of the site is also irregular, thereby reducing public interest in accessing the website. In fact, through the study program website you can disseminate information such as profiles, vision and mission, organizational structure, scholarships, student achievements, questionnaires, and news content and other information. Therefore, it is necessary to manage the Indonesian Literature Study Program website at Jambi University as a medium of information for the public. This website management activity begins with the stages of analyzing website needs, collecting website data, designing and filling content, and socializing the website to the public. The result of this service activity is website governance Jambi University's Indonesian Literature Study Program is getting better. This can be seen from the more organized appearance of the website, the latest information that is continuously updated, and the positive response from website users.